Rich democracies : political economy, public policy, and performance - Wilensky, Harold L. (University of California Press, 2002)
Drawing on data covering the past 50 years and more than 400 interviews with top decision-makers, Wilensky provides a richly detailed account of the common problems modern governments confront and their contrasting styles of conflict resolution.